2021
DOI: 10.4103/tcmj.tcmj_288_20
|View full text |Cite
|
Sign up to set email alerts
|

The link between abnormalities of calcium handling proteins and catecholaminergic polymorphic ventricular tachycardia

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT), a rare autosomal dominant or recessive disease, usually results in syncope or sudden cardiac death. Most CPVT patients do not show abnormal cardiac structure and electrocardiogram features and symptoms, usually onset during adrenergically mediated physiological conditions. CPVT tends to occur at a younger age and is not easy to be diagnosed and managed. The main cause of CPVT is associated with mishandling Ca 2+ in cardiomyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…In fact, and experimental optical mapping study in heart by Němec and co-workers suggested that the abnormal Ca 2+ dynamics associated with CPVT, can also be associated with the T-wave lability found in LQT [58]. The underly defect in the Ca 2+ dynamics is the Ca 2+ overload in the myocyte for both LQT and CPVT4 [59,60]. For less severe CaM mutations, the deviation from the wild-type action potential would be difficult to detect using available diagnostic methods, and a mutation which only fractionally decreases the CaM-dependent LCC transition to a closed state would avoid detection in the unstimulated heart.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, and experimental optical mapping study in heart by Němec and co-workers suggested that the abnormal Ca 2+ dynamics associated with CPVT, can also be associated with the T-wave lability found in LQT [58]. The underly defect in the Ca 2+ dynamics is the Ca 2+ overload in the myocyte for both LQT and CPVT4 [59,60]. For less severe CaM mutations, the deviation from the wild-type action potential would be difficult to detect using available diagnostic methods, and a mutation which only fractionally decreases the CaM-dependent LCC transition to a closed state would avoid detection in the unstimulated heart.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of cardiomyopathy markers, particularly titin and troponin T, is reduced in Rgs2/5 dbKO hearts of both sexes, and individual cardiomyocyte contractions are markedly decreased despite increased mobilization of intracellular Ca 2+ . The augmented Ca 2+ mobilization, however, appears to contribute to arrhythmogenesis as Ca 2+ recycling is impaired, leading to prolonged elevation of cytoplasmic Ca 2+ concentration, which is known to be arrhythmogenic [ 30 , 52 - 54 ]. Taken together with the decrease in the expression of contractile genes, our data suggest that the cardiomyopathy in Rgs2/5 dbKO is accompanied by unraveling of the mechanisms that couple cardiac electrical excitation and contractility, thereby contributing to the marked decrease in baseline ejection fraction and fractional shortening.…”
Section: Discussionmentioning
confidence: 99%